A GTP-driven motor moves proteins across the outer envelope of chloroplasts - Schleiff, Enrico (The National Academy of Sciences, 2003)
The translocation of proteins across cellular membranes is a key mechanistic problem for every cell. The preprotein translocon at the chloroplast outer envelope is responsible for precursor protein recognition and translocation across the outer envelope. We have reconstituted the translocation process into proteoliposomes from single subunits or by using the purified translocon. Precursor proteins are recognized by the Toc34 receptor in an initial GTP-dependent process. Translocation across the plane of the membrane then occurs through the Toc75 channel in a GTP-dependent process. Correspondingly, GTP hydrolysis of Toc proteoliposomes is 100-fold enhanced in the presence of preprotein. Complete translocation is demonstrated by processing of the precursor form to the mature form by the stromal processing peptidase and by protease resistance of the imported protein. Molecular chaperones are not involved in this translocation event. We show that Toc159 acts as a GTP-driven motor in a sewing-machine-like mechanism.